Improving German Speaking Skills Through Contextual Teaching And Learning - Misnah Mannahali (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. This study aims to investigate the influence of contextual teaching and learning (CTL) in improving German speaking skills. This was an action classroom research conducted in two cycles. The data were the results of cycle 1 and cycle 2. The results of the study showed that the implementation of CTL influenced and could improve students’ German speaking skills. The results suggest that CTL can be applied in German language teaching and learning, especially German speaking skills. Keywords: Speaking, German, Contextual Teaching and Learning